Angolan cymbopogon citratus used for therapeutic benefits: nutritional composition and influence of solvents in phytochemicals content and antioxidant activity of leaf extracts - Soares, Marta O. (2014)
Folk medicine is a relevant and effective part of indigenous healthcare systems which are, in practice, totally dependent on traditional healers. An outstanding coincidence between indigenous medicinal plant uses and scientifically proved pharmacological properties of several phytochemicals has been observed along the years. This work focused on the leaves of a medicinal plant traditionally used for therapeutic benefits (Angolan Cymbopogon citratus), in order to evaluate their nutritional value. The bioactive phytochemical composition and antioxidant activity of leaf extracts prepared with different solvents (water, methanol and ethanol) were also evaluated. The plant leaves contained ~60% of carbohydrates, protein (~20%), fat (~5%), ash (~4%) and moisture (~9%). The phytochemicals screening revealed the presence of tannins, flavonoids, and terpenoids in all extracts. Methanolic extracts also contained alkaloids and steroids. Several methods were used to evaluate total antioxidant capacity of the different extracts (DPPH; NO; and H2O2 scavenging assays, reducing power, and FRAP). Ethanolic extracts presented a significantly higher antioxidant activity (p < 0.05) except for FRAP, in which the best results were achieved by the aqueous extracts. Methanolic extracts showed the lowest radical scavenging activities for both DPPH; and NO; radicals.